Molecular epidemiology and genomic features of Bordetella pertussis in Tianjin, China, 2023 - Xiaohui Lu; Wen Li; Xuan Chen; Wei Zhang; Aiping Yu; Guangwen Liu; Baolu Zheng; Xin Gao; Yamin Liu; Xiaoyan Li (BMC Microbiology)
Abstract Background Pertussis, a highly contagious respiratory disease caused by Bordetella pertussis (BP), poses challenges due to genomic variation that may contribute to its persistence in vaccinated populations and the development of antimicrobial resistance. Methods In this study, we characterized 27 BP isolates collected from Tianjin, China in 2023, using whole-genome sequencing and multilocus genotyping (MGT) to explore their genomic diversity. For comparative analysis, we selected 165 international BP genomes to examine the genomic diversity and evolutionary traits of Tianjin strains within a global context. Results The results revealed that all 27 isolates belonged to ST2 (100.0%), with no distinct phylogenetic clustering observed. Furthermore, phylogenetic analysis integrating 165 global BP genomes indicated that the Tianjin strains exhibited high genomic homogeneity with globally circulating strains. Specifically, 16 isolates (59.3%) carried the virulence genotype ptxA-1/ptxC-4/ptxP-3/prn-150(truncated)/fim2-1/fim3-1/fhaB-1, while 11 isolates (40.7%) carried the genotype ptxA-1/ptxC-4/ptxP-3/prn150/fim2-1/fim3-1/fhaB-1. Additionally, all 27 isolates exhibited complete resistance to erythromycin, azithromycin, clarithromycin, and clindamycin, whereas 18.5% of them were resistant to levofloxacin. Conclusions This study elucidates the phylogenetic, genomic characteristics, and drug sensitivity profiles of BP strains isolated in Tianjin, China, in 2023, providing valuable insights into BP persistence in vaccinated populations.